Preliminary study of second harmonic generation in poled Teo2-Nb2o5-Li2o-Sm2o3 glass - Rohani, Md. Supar; Khamis, Noorzana; Sahar, Md. Rahim (Faculty of Science, University Teknologi Malaysia, 2008)

(untitled)
Series of glass based on teo2-nb2o5-li2o-sm2o3 of 1mm thick is electrically thermal poled around 270°c (120°c below transition glass temperature, tg), for 1 hour under applied de field of 2.5kv. The micrograph taken under sem shows that the poling caused small particles occurs at voltage of 2.5kv on anode-side surface. Second order optical nonlinearities will be induced in tellurite glasses by the thermal poling technique. The induced will be measured via second harmonic generation using a fundamental beam from a 1064 nm mode locked nd: yag laser. The nonlinear regions will be characterized using the maker-fringe technique, in which the second harmonic signals were observed as a function of incident angle of the fundamental beam. The profile has contributions from a distinct region: a near-anodic surface